DWUDZIESTOLECIE POLITYKI PIENIĘŻNEJ NBP WPŁYW TRANSFORMACJI I INTEGRACJI GOSPODARCZEJ - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 2009)
The paper demonstrates the scale o f transformations taking place in the central bank’s monetary policy between 1989 and 2009. The National Bank o f Poland needed to be transformed in a modern central bank, capable o f functioning in a market economy. In order to facilitate that, various legal and institutional changes needed to be made and the existing laws required necessary amendments. They are analysed and presented in the paper. Next, the eclectic monetary policy that the Bank pursued in the years 1990-1997 is described, and its strong and weak points identified. After that the new strategy, continued till date, focused on inflation targeting is discussed and its effects and reasons for implementation, as well reasons why inflation is hard to control in Poland, explained. The paper ends with a description of the evolution o f the tools and instruments used by the National Bank o f Poland in the last twenty years.
TWENTY YEARS OF THE NATIONAL BANK OF POLAND’S MONETARY POLICY: IMPACT OF THE ECONOMIC TRANSFORMATION AND INTEGRATION